RETRACTED: Integrating the Role of Green Fiscal Policies With Energy Prices Volatility and Energy Efficiency: Presenting a COVID-19 Perspective - Yin, Qingyan; Anser, Muhammad Khalid; Abbas, Shujaat; Ashraf, Junaid; Ahmad, Munir; Jamshid, Junaid; Osabohien, Romanus (Frontiers in Energy Research, 2022)
Energy and other related sectors are changing in China. The study inferred estimating the energy product price volatility with energy efficiency during COVID-19 with the role of green fiscal policies. For this, we applied unit-root tests, ADCC-GARCH, and CO-GARCH techniques to infer the study findings. The results showed that energy price volatility is significantly connected during 2018. More so, the green fiscal policies are significantly connected between energy product price volatility and energy efficiency during COVID-19 (2019-2020). From energy products, the crude oil price volatility is significant with 16.4%, heating oil volatility is significant with 18.2%, natural oil price volatility is 9.7%, gasoline price volatility is 28.7%, and diesel price volatility is 34.1% significant with energy efficiency, due to intervening role of green fiscal policies. The findings of the study are robust in comparison to previous studies. Multiple stakeholders can take guidelines from the findings of a recent study. As per our best understanding and knowledge, if suggested recommendations are implemented effectively, these results will help to enhance energy efficiency through green fiscal policies in the post-covid-period.